Effect of cigarette smoke extract on the intestinal microenvironment of ulcerative colitis tissue. Issue 6 (21st October 2020) - Cannon, Aoife; Clarke, Niamh; MacCarthy, Finbar; Dunne, Cara; Kevans, David; Mahmud, Nasir; Lysaght, Joanne; O'Sullivan, Jacintha
Abstract: Background and Aim: Ulcerative colitis (UC) is an autoimmune disease characterized by inflammation in the gastrointestinal tract. The severity of UC is higher in nonsmokers than smokers; however, the biological mechanisms controlling this effect remain unknown. The aim of this study was to examine the effect of cigarette smoke extract (CSE) on inflamed and noninflamed colonic tissue from UC patients and to determine if inflammatory mediators, transcription factors, and T cell phenotypes are altered by CSE. Methods: Blood and colonic biopsies were obtained from UC patients undergoing endoscopy. Biopsies were cultured in the presence or absence of CSE. Multiplex enzyme‐linked immunosorbent assay (ELISA) measured secreted levels of inflammatory mediators. Nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) and Hypoxia‐inducible factor 1‐alpha (HIF‐1α) expression were measured by DNA‐binding ELISA. T cell phenotypes were assessed by flow cytometry in matched blood and biopsies. Results: Secreted levels of interleukin 2 (IL‐2), interleukin 6 (IL‐6), tumor necrosis factor ‐ alpha (TNF‐α), chemokine (C‐C motif) ligand 2 (CCL2), and interleukin 10 (IL‐10) were significantly (all P < 0.05) decreased following treatment with CSE. This effect was specific to inflamed tissue and was not observed in noninflamed tissue. CSE did not alter the expression of NF‐κB or HIF‐1α. Assessment of T cell phenotypes in blood and tissue revealed that there were significantly more activated and exhausted T cells in the colonic tissue compared to matched blood. These profiles were not altered following CSE treatment. Conclusion: These data suggest that observed effects of CSE in reducing inflammatory mediators ex vivo are specific to inflamed colonic tissue but are not due to the activation of NF‐κB or HIF‐1α and are not caused by alterations in subpopulations of T cells in these UC tissues. Abstract : This study identifies, for the first time, that cigarette smoke extract reduces the secretion of CCL2, IL‐2, IL‐6, IL‐10, and TNF‐a in the inflamed (but not the matched noninflamed) colonic tissue of UC patients. Furthermore, this effect was not due to the activation of the transcription factors NF‐κB or HIF‐1a.